Alice Bliss - HARRINGTON, Laura, 1953- (Pamela Dorman Books/Viking, 2011)
When Alice Bliss learns that her father is being deployed to Iraq, she's heartbroken. Alice idolizes her father, loves working beside him in their garden, accompanying him on the occasional roofing job, playing baseball. When he ships out, Alice is faced with finding a way to fill the emptiness he has left behind. Matt will miss seeing his daughter blossom from a tomboy into a full-blown teenager. Alice will learn to drive, join the track team, go to her first dance, and fall in love, all while trying to be strong for her mother, Angie, and take care of her precocious little sister, Ellie.